Proceedings From the First International Workshop at Sidra Medicine: “Engineered Immune Cells in Cancer Immunotherapy (EICCI): From Discovery to Off-the-Shelf Development”, 15th–16th February 2019, Doha, Qatar - Guerrouahen, Bella; Elnaggar, Muhammad; Al-Mohannadi, Anjud; Kizhakayil, Dhanya; Bonini, Chiara; Benjamin, Reuben; Brentjens, Renier; Buchholz, Christian J.; Casorati, Giulia; Ferrone, Soldano; Locke, Frederick L.; Martin, Francisco; et al. (Frontiers in Immunology, 2021)
The progress in the isolation and characterization of tumor antigen (TA)-specific T lymphocytes and in the genetic modification of immune cells allowed the clinical development of adoptive cell therapy (ACT). Several clinical studies highlighted the striking clinical activity of T cells engineered to express either Chimeric Antigen (CAR) or T Cell (TCR) Receptors to target molecularly defined antigens expressed on tumor cells. The breakthrough of immunotherapy is represented by the approval of CAR-T cells specific for advanced or refractory CD19+ B cell malignancies by both the Food and Drug Administration (FDA) and the European Medicinal Agency (EMA). Moreover, advances in the manufacturing and gene editing of engineered immune cells contributed to the selection of drug products with desired phenotype, refined specificity and decreased toxicity. An important step toward the optimization of CAR-T cell therapy is the development of “off-the shelf” T cell products that allow to reduce the complexity and the costs of the manufacturing and to render these drugs available for a broad number of cancer patients. The Engineered Immune Cells in Cancer Immunotherapy (EICCI) workshop hosted in Doha, Qatar, renowned experts, from both academia and industry, to present and discuss the progress on both pre-clinical and clinical development of genetically modified immune cells, including advances in the “off-the-shelf” manufacturing. These experts have addressed also organizational needs and hurdles for the clinical grade production and application of these biological drugs.